Structural and functional biology of arachidonic acid 15-lipoxygenase-1 (ALOX15) - Ivanov, Igor (Gene, 2015)
Lipoxygenases (LOX) form a family of lipid peroxidizing enzymes, which have been implicated in a number of physiological processes and in the pathogenesis of inflammatory, hyperproliferative and neurodegenerative diseases. They occur in two of the three domains of terrestrial life (bacteria, eucarya) and the human genome involves six functional LOX genes, which encode for six different LOX isoforms. One of these isoforms is ALOX15, which has first been described in rabbits in 1974 as enzyme capable of oxidizing membrane phospholipids during the maturational breakdown of mitochondria in immature red blood cells. During the following decades ALOX15 has extensively been characterized and its biological functions have been studied in a number of cellular in vitro systems as well as in various whole animal disease models. This review is aimed at summarizing the current knowledge on the protein-chemical, molecular biological and enzymatic properties of ALOX15 in various species (human, mouse, rabbit, rat) as well as its implication in cellular physiology and in the pathogenesis of various diseases.